Development of Assignment-Based Teaching Materials And Local Wisdom For English Learning of Iisbud Sarea Students During the Pandemic - Samsudin Samsudin; Sukarismanti Sukarismanti (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2021)
The purpose of this research is to develop assignment-based teaching materials and local wisdom for the English language learning of Iisbud Sarea students during the pandemic. Then, this research method uses the ADDIE namely development, analysis, design, development, implementation, and evaluation. The results showed that the validation test results of material expert, language expert, and media expert against the modules developed were in the "high" and "very high" categories. Then, the results of the practicality test both in terms of students and English lecturer that the module is in the category of "practical" and "very practical". While the effectiveness test showed that the assignment-based English module and local wisdom are in the practical category where the test results in the law study program are 16 people who get a score of ≥ 70 or 76.2%. While the test results in the sociology study program are 15 people who get a score of ≥ 70 or 77%. Thus, overall the assigment-based English language module and local wisdom are in the effective category and have met the standard of the effectiveness of pre-determined teaching materials, namely 75% of students get a grade of ≥ 70 or grade B.